Measuring Violence Against Children: A COSMIN Systematic Review of the Psychometric Properties of Child and Adolescent Self-Report Measures - Meinck, F.; Neelakantan, L.; Steele, B.; Jochim, J.; Davies, L.M.; Boyes, Mark; Barlow, J.; Dunne, M. (SAGE PUBLICATIONS INC, 2023)
Research on violence against children (VAC) requires meaningful, valid, and reliable self-report by children. Many instruments have been used globally and decisions to select suitable measures are complex. This review identifies child and adolescent self-report measures that are most likely to yield valid, reliable, and comparable data in this field. A systematic review (PROSPERO: CRD4201706) was conducted using the 2018 Consensus-based Standards for the selection of health Measurement Instrument (COSMIN) criteria. Six electronic databases and gray literature were searched. Manuscripts published in English and describing the development and psychometric qualities of child/adolescent self-report instruments were included. Thirty-nine original instruments and 13 adaptations were identified in 124 studies. The quality of evidence ranged from “very low” to “high” depending on the measure and the psychometric properties assessed. Most measures were not widely used, and some have been applied in many settings despite limited evidence of their psychometric rigor. Few studies assessed content validity, particularly with children. The ACE, CTQ, CTS-PC, CECA, ICAST, and JVQ have the best psychometric properties. An overview of items measuring frequency, onset, duration, perpetrators, and locations is provided as well as an assessment of the practicalities for administration to help researchers select the instrument best suited for their research questions. This comprehensive review shows the strengths and weaknesses of VAC research instruments. Six measures that have sufficient psychometric properties are recommended for use in research, with the caveat that extensive piloting is carried out to ensure sufficient content validity for the local context and population.